Prevalence of malnutrition among U5 children in Iraqi south governorate (Basrah, Thi Qar and Misan) - Mahdi, K.M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The field work to study morbidity & nutritional status of 3828 child aged between 659 months in Basra, Misan and Thi Qar governorate.  The results indicated that 14%, 11.7% and 5.4% of the children suffer from diarrhea, Fever & Acute Respiratory Infection (API) respectively. While the prevalence of malnutrition for the children at the three governorate indicated that the chronic was 24.8%, 25.1% and 23%, general malnutrition was 17.1%, 21.4% and 22% where as the acute malnutrition was 9.2, 9.4 and 14.2 respectively.